Loss of Predator Discrimination by Critically Endangered Vancouver Island Marmots Within Five Generations of Breeding for Release - Dixon-MacCallum, Graham P.; Rich, Johnathan L.; Lloyd, Natasha; Blumstein, Daniel T.; Moehrenschlager, Axel (Frontiers in Conservation Science, 2021)
Conservation translocations, which involve the intentional movement and release of organisms for conservation benefit, are increasingly required to recover species of conservation concern. Behavioral suitability of animals to maximize post-release survival is important to accomplish conservation translocation objectives. The Vancouver Island marmot (Marmota vancouverensis) is a critically endangered endemic in Canada which has been captive-bred for 24 years for reintroductions and reinforcements that have increased the wild population from approximately 30 to more than 200 individuals. Despite this success many marmots are killed by predators after release and predation represents a major hurdle to full marmot recovery. To better understand if captive-bred marmots are prepared for the novel environment into which they will be released, and to determine whether such suitability changes over time, we presented taxidermy mounts of mammalian predators and non-predators to marmots that were wild-caught, and captive born for between one and five generations. We also examined mortality of offspring from marmots we tested that had been released to the wild. A minimum of 43% of offspring were killed by predators in the wild over 17 years, most by cougars. Marmots in captivity generally responded to taxidermy mounts by decreasing foraging and increasing vigilance, and overall responded more strongly to predators than non-predators, especially wolves. However, marmots in captivity for more than two generations lacked discrimination between cougars, non-predators, and controls, suggesting a rapid loss of predator recognition. This study was only possible because predator-recognition trials were initiated early in the conservation translocation program, and could then be repeated after a number of generations. The finding that changes occurred relatively rapidly (within five generations during which changes in genetic diversity were negligible) suggests that behavioral suitability may deteriorate more rapidly than genetics would suggest. Strategies addressing potential behavior loss should be considered, including sourcing additional wild individuals or pre-release training of captive-born individuals. Subsequently, post-release survival should be monitored to determine the efficacy of behavior-optimization strategies.